Pendampingan Belajar untuk Anak-Anak sebagai Upaya Peningkatan Motivasi Belajar Matematika Sejak Dini - Awatif, Awatif; Yulianti, Eni; Susanti, Ade; Riyadi, Sugeng; Wulandari, Eko (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Mathematics tutoring is motivated by children's low motivation and mathematical abilities. Tutoring is an activity provided by experts to help individuals face and solve problems related to learning. Therefore, this service activity aims to increase motivation to learn mathematics from an early age. The hope is that if the motivation to learn is good, then the learning results will also be good. The service activity involved 31 people. The method used is collaborative learning. Where students discuss in groups to solve mathematical problems. The result of this program is that students seemed more enthusiastic about learning during the activity. This is reflected in when doing the homework given by the teacher, students are more enthusiastic. At the end of the activity, students are given questions to measure the success of the tutoring activity. Of the 31 people, there were 87% of students with learning results above 75. Apart from that, students admitted that with tutoring activities students were more motivated in learning mathematics. Consequently, it can be concluded that tutoring activities can foster learning motivation and overcome difficulties in understanding mathematics. The impact of this activity is that the students are motivated to learn mathematics so that it can improve their performance and score.